The Emotional Experiences of Indonesian PhD Students Studying in Australia during the COVID-19 Pandemic - Supiani,; Rafidiyah, Dina; Yansyah,; Nadia, Hafizhatu (Journal of International Students, 2020)
This narrative study aims to explore the emotional experiences of two Indonesian students pursuing a doctorate (PhD) degree in Australia during the COVID-19 pandemic. Drawing on semi-structured interview data, we found that the prevalence of COVID-19 affected the participants’ emotions and behaviors. Both participants experienced different emotions and behaviors in facing various challenges during the pandemic. The study stresses the importance of independence, family support, social support, and university support that the participants needed to reduce their anxiety and stress due to some social restrictions during the outbreak of COVID-19, especially for those who are extrovert.